Ambiente de programação para crianças das séries iniciais - NewProg+ - Costa, Cleziel Franzoni da (2017)
This work presents NewProg+, a digital environment for children in the early grades to learn computer programming. NewProg+ has an activity editor for use by educators and a Visual Programming Language (LVP) and program evaluator for use by apprentices. NewProg+ is an update of the NewProg environment and differs from it, especially by including repetition structures, condition tests and subprograms in its visual programming language. Learning computer programming exercises a variety of skills in children, such as logical thinking and problem solving skills, and in the tests with the LVP presented, it was possible to prove that the students were able to program their solutions in the NewProg+.This work presents NewProg+, a digital environment for children in the early grades to learn computer programming. NewProg+ has an activity editor for use by educators and a Visual Programming Language (LVP) and program evaluator for use by apprentices. NewProg+ is an update of the NewProg environment and differs from it, especially by including repetition structures, condition tests and subprograms in its visual programming language. Learning computer programming exercises a variety of skills in children, such as logical thinking and problem solving skills, and in the tests with the LVP presented, it was possible to prove that the students were able to program their solutions in the NewProg+.